SISTEM INFORMASI PERPUSTAKAAN PADA SMA SANTO ANTONIO ALAS BERBASIS WEBSITE MENGGUNAKAN METODE PROTOTYPE - Gervasio Pedro Ribeiro Fernandesv; Evy Sophia; Tubagus Mohammaa Akhriza (Dinamika Dotcom : Jurnal Pengembangan Manajemen Informatika dan Komputer, 2025)
SMA Santo Antonio is a senior high school educational institution. Every educational institution is required to have a library as part of its facilities, which serves to enhance students' literacy. In the library of SMA Santo Antonio, the book borrowing system is already in place; however, the current system uses manual record-keeping, which has several drawbacks. These include a lack of efficiency in entering book borrowing data, as the library staff must manually write the data into a logbook. Due to this manual data recording method, there is sometimes a loss of record data, which complicates future data reconciliation. The solution to this problem is to computerize the existing conventional system. By using a web-based application, it is expected to facilitate the library staff in entering and recording library data, which will be stored digitally to minimize data loss. The SDLC method with a prototype approach is the method used in this research. The researcher analyzes the problems in the current system to identify solutions, followed by testing the developed application. The result of this research is a library application that benefits library staff in data entry and data processing in the school library.